MANAJEMEN LITERASI BERBASIS MEDIA TEKNOLOGI INFORMASI DI SEKOLAH DASAR (SD) NEGERI 11 LALEMBUU KABUPATEN KONAWE SELATAN - Akib, Akib; Fanani, Eka Riri (UIN Imam Bonjol Padang, 2021)
This research aims to analyze Information Technology Media-based Literacy Management is a governance program for literacy activities using a variety of information technology media held at the 11th Elementary School of Lalembuu, Konawe Selatan Regency, Southeast Sulawesi Province. Management or governance in this activity program includes Planning, Organizing, Implementing and Evaluating Activities. The initial motivation of this activity program was the existence of School Operational Assistance Funds (BOS) that were received by schools that were used to meet the needs of various types of information technology media. This research is a qualitative research with the object of management study an activity program. The approach that researchers use is a qualitative descriptive approach. Data collection techniques in this study were through observation, documentation and interviews. While the method used in this research is descriptive data analysis method of observations, documentation and interviews in the field. The results showed that there was a literacy program using various types of information technology media held at Lalembuu State Elementary School 11. The various types of information technology media in question consist of hardware in the form of computers, routers, Android phones, focus, laptops and software in the form of Rumah Belajar applications available online and offline. In governance these activities consist of Planning, Organizing, Implementing and Evaluating Activities. Simple, practical, effective and efficient management turns out to be a major factor in achieving the objectives of this activity program.